Field guide for research in community settings tools, methods, challenges and strategies - Rezaul Islam, M. (Elgar field guides, 2021)
"This insightful book offers practical advice to fieldworkers in social research, enabling robust and judicious applications of research methods and techniques in data collection. It also outlines data collection challenges that are commonly faced when working in the field. Authors address key strategies to tackle the major challenges to fieldwork, including advice on using indigenous or innovative skills and making intelligent use of the advantages already available within standard research methodologies. International contributors provide a hands-on account of research methodologies as applied in the field, with particular focus on research ethics and community culture and interactions. The book offers a number of useful case studies, featuring examples of the application of research techniques in different cultural and socioeconomic contexts. Utilising an innovative and dynamic 'story telling' method, this book will be a useful research tool for fieldworkers engaging in social science research in community settings, as well as students in the field learning the core techniques of fieldwork" -- Provided by publisher.